PENGARUH AMANDEMEN KEEMPAT UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 TERHADAP PEMERINTAHAN DAERAH - Ni Kadek Rudiani (University of Udayana, 2017)
The laws of The Republic Of Indonesia in 1945 became the highest legal source of lower legal products. The laws of The Republic Of Indonesia in 1945 from 1999 to 2002 have been amended four times. The consequences of the amendement certainly affect the laws that run it including synchronzation of local government law with the result of the amendment of the four constitutions of The Republic Of Indonesia in 1945. In this connection the formulation of this research problem is: a) How is the regulation of local government in the amendnment of the four laws of The Republic of Indonesia in 1945?, b) what the arrangement of local government after the amendnment of the four laws of The Republic of Indonesia in 1945?. Is normative legal research. As is known, normative legal research includes research on legal principles, legal system, legal synchronization level, and legal history research. In accordance with the characteristics and nature of normative law research, in this study will use several methods of approach: The Statue Approach (statutory approach, The analitical and Conseptual Approach) Based on Article 18 of the 1945 Constitution of the State of the Republic of 1945 found The existence of development policy relation between central government and regional government as regulated in Law Number 23 Year 2014 about Local Government, that is base on: Decentralization, Deconcentration and Co-Administration, assignment from government to region and village and from region to village To perform certain tasks accompanied by financing, facilities and infrastructure and human resources with the obligation to report in its implementation and accountable to the commissioned. Undang-Undang Negara Republik Indonesia Tahun 1945 menjadi sumber hukum tertinggi produk hukum yang lebih rendah. Undang-Undang Negara Republik Indonesia Tahun 1945 dari Tahun 1999 sampai 2002 telah dilakukan amandemen sebanyak empat kali. Konsekwensi dari amandemen tersebut tentunya berpengaruh terhadap Undang-Undang yang menjalankannya termasuk sinkronisasi Undang-Undang Pemerintahan Daerah dengan hasil Amandemen Keempat Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Dalam kaitan itu rumusan masalah penelitian ini adalah: a) Bagaimana pengaturan pemerintahan daerah dalam Amandemen Keempat Undang-Undang Negara Republik Indonesia Tahun 1945?, b) Bagaimana pengaturan pemerintahan daerah dalam Undang-Undang Pemerintahan Daerah pasca Amandemen Keempat Undang-Undang Negara Republik Indonesia Tahun 1945?. Jenis penelitian ini adalah penelitian hukum normatif. Sebagaimana diketahui penelitian hukum normatif mencakup penelitian terhadap asas-asas hukum, sistematika hukum, taraf sinkronisasi hukum, dan penelitian sejarah hukum. Sesuai dengan karakteristik dan sifat penelitian hukum normatif, maka dalam penelitian ini akan memakai beberapa metode pendekatan: The Statue Approach (pendekatan perundang-undangan), The analitical and Conseptual Approach (pendekatan analisis konsep hukum). Berdasarkan Pasal 18 Undang-Undang Dasar Negara Republik 1945 ditemukan adanya hubungan kebijaksanaan pembangunan antara pemerintah pusat dan pemerintahan daerah sebagaimana diatur dalam Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah, yaitu dengan dasar-dasar : Desentralisasi, Dekonsentrasi, dan Tugas pembantuan, penugasan dari pemerintah kepada daerah dan desa dan dari daerah ke desa untuk melaksanakan tugas tertentu yang disertai pembiayaan, sarana dan prasarana serta sumber daya manusia dengan kewajiban melaporkan dalam pelaksanaannya dan mempertanggungjawabkan kepada yang menugaskan.